Financial Market Development and Foreign Portfolio Investments in Nigeria and South Africa - Olubodun, Abayomi Omoshola; Ogbebor, Peter Ifeanyi; Wale-awe, Isaac (Archives of Business Research, 2024)
The study investigates the effect of financial market development on foreign portfolio investment in Nigeria and South Africa between the periods of first quarter in 1995 to fourth quarter of 2022. The study employs an ex-post factor research design, the study deploys panel autoregressive distributed lag modelling. The inferences were made at 5% significant level. Findings from the study reveal that lagged Portfolio Investment is not statistically significant to foreign portfolio investment (coefficient = -0.5026613, p-value = 0.275), in contrast, lagged Stock Market Turnover Ratio has a significant positive coefficient (coefficient = 0.5696119, p-value < 0.000), indicating a positive short-term relationship with changes in Portfolio Investment. However, other lagged variables like Stock Market Capitalization, All Share Index, Broad Money Supply, and Real Credit to the Private Sector show coefficients without statistical significance, suggesting limited short-term predictive power. In the long run, the adjusted term for lagged Portfolio Investment exhibits a highly significant negative effect (coefficient = -1.502661, p-value = 0.001). Lagged Broad Money Supply and Real Credit to the Private Sector also lack statistical significance in the long term, while lagged Stock Market Turnover Ratio and All Share Index have statistically significant positive coefficients. However, Stock Market Capitalization lacks statistical significance in predicting long-term changes in foreign Portfolio Investment. In respect to the result, the study recommended that policy makers should implement measures to enhance transparency and regulation within financial markets to promote investor confidence and attract foreign capital inflows. This may include strengthening regulatory frameworks, improving reporting standards, and ensuring effective oversight mechanisms.